Characteristic of electrical signal of transient luminous events (TLES) in Pekan Pahang - Mohamed, Amir Izzani; Daud, Mohd Razali; Noordin, Nurul Hazlina; Saari, Mohd Mawardi; Ibrahim, Wan Ismail (2020)
Lightning is a phenomenon occurring over the atmospheric area. Transient luminous events (TLE) is a kind of lightning incident that exceeds the speed of lightning in a lightning strike event. It is very difficult to spot the occurrence and it happens in a very short period of time. Thus, a high-frame-rate photo frame is required. This project examines the probability of occurrence of transient luminous events and positive cloud to ground (+CG) above Kuala Lumpur by using a monochrome camera. Transient luminous events are divided into several types such as Elves, Sprites, Halo (Halos), Blue Jets, and Gigantic Jets. This incident was detected using a monochrome camera facing the direction of Kuala Lumpur from Pekan with an altitude of 20 km altitude so that the incident could be recorded clearly and its features could be analyzed and categories with video and frames recorded. The recorded videos have been extracted into photos frame by frame. Thousands of photos extracted were examined one by one to get the result as transient luminous events and +CG phenomenon only happened in a few milliseconds. The study reveals that it is possible to have Transient luminous events above the atmospheric area in Malaysia. Jets and Halos have been captured by using high frame rate monochrome camera.